Silent mating‐type information regulation 2 homolog 1 overexpression is an important strategy for the survival of adapted suspension tumor cells. Issue 9 (11th August 2019) - Park, Ji Young; Han, Sora; Ka, Hye In; Joo, Hyun Jeong; Soh, Su Jung; Yoo, Kyung Hyun; Yang, Young
Abstract: Characterization of circulating tumor cells (CTC) is important to prevent death caused by the metastatic spread of cancer cells because CTC are associated with distal metastasis and poor prognosis of breast cancer. We have previously developed suspension cells (SC) using breast cancer cell lines and demonstrated their high metastatic potential. As survival of CTC is highly variable from a few hours to decades, herein we cultured SC for an extended time and named them adapted suspension cells (ASC). Silent mating‐type information regulation 2 homolog 1 (SIRT1) expression increased in ASC, which protected the cells from apoptosis. High SIRT1 expression was responsible for the suppression of nuclear factor kappa B (NF‐κB) activity and downregulation of reactive oxygen species (ROS) in ASC. As the inhibition of NF‐κB and ROS production in SIRT1‐depleted ASC contributed to the development of resistance to apoptotic cell death, maintenance of a low ROS level and NF‐κB activity in ASC is a crucial function of SIRT1. Thus, SIRT1 overexpression may play an important role in growth adaptation of SC because SIRT1 expression is increased in long‐term rather than in short‐term cultures. Abstract : We found that silent mating‐type information regulation 2 homolog 1 (SIRT1) expression increased in adapted suspension cells (ASC) wherein it protected cells from apoptosis. SIRT1 high expression was responsible for the suppression of nuclear factor kappa B (NF‐κB) activity and downregulation of reactive oxygen species (ROS) in ASC.